Friction vs.
The friction material composition with a carbonaceous lubricant and inorganic modifiers addresses the stability and wear resistance issues in disc brake pads, ensuring effective braking performance with stainless steel disc rotors.
Patent Information
- Application Number
- JP2022531709
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-06-16
- Filing Date
- 2021-06-09
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2041-06-09
AI Technical Summary
Existing disc brake pads and stainless steel disc rotors face challenges in maintaining brake effectiveness stability and friction material wear resistance due to the decomposition of organic substances at high temperatures and reduced braking loads in electric and hybrid vehicles.
A friction material composition is developed without copper and iron-based metal fibers, incorporating a carbonaceous lubricant (10-15%) and inorganic friction modifiers (15-30%) with Mohs hardness of 6 or more, along with a thermal conductivity of 1.2-3.0 W/m·K, to enhance heat dissipation and grinding action.
The solution provides improved brake effectiveness stability and wear resistance by suppressing thermal decomposition and enhancing lubrication, resulting in a stable and durable friction pair with stainless steel disc rotors.
Smart Images

Figure 0007616804000001 
Figure 0007616804000002 
Figure 0007616804000003
Abstract
Description
[Technical field]
[0001] The present invention relates to friction pairs, and more particularly to friction pairs for use in vehicles such as passenger cars. [Background technology]
[0002] 2. Description of the Related Art Conventionally, disc brake pads having a friction material attached to a metal base member have been used as friction members for disc brakes in passenger vehicles.
[0003] In recent years, there has been a demand for quieter brakes, and so disc brake pads using a friction material called NAO material, which produces less brake noise, have come into widespread use.
[0004] The NAO friction material is a material obtained by molding a friction material composition containing a binder, a fiber base material other than steel-based fibers such as steel fibers or stainless steel fibers, and a friction modifier, and is classified as a friction material along with semi-metallic friction materials and low-steel friction materials that contain steel-based fibers as a fiber base material. In recent years, due to legal restrictions on the copper content in the United States, the development of friction materials that contain only 5% by weight or less of copper or that do not contain any copper at all has become common.
[0005] Patent Document 1 describes a friction material composition containing a fibrous base material, a friction modifier, and a binder, in which the copper content in the friction material composition is 0.5 mass % or less in terms of elemental copper, and the friction material composition contains granular titanate as the friction modifier, in which titanate is made into granules, and the average particle size of the granular titanate is 100 to 250 μm, and a friction material obtained by molding the friction material composition.
[0006] Patent Document 2 describes a friction material composition that contains a fiber base material, an inorganic filler, an organic filler, and a binder, and has a copper content of 0.5 mass % or less, in which the inorganic filler includes an abrasive having an average particle diameter of 3 to 5 μm and an abrasive having an average particle diameter of 9 to 13 μm, and the inorganic filler includes a titanate having an average particle diameter of 1.5 to 4.5 μm and a titanate having an average particle diameter of 15 to 45 μm.
[0007] As a mating material for disc brake pads equipped with such friction materials containing almost no copper components, disc rotors made of cast iron are used as described in Patent Document 3. Such cast iron disc rotors have a problem of low corrosion resistance and rusting during use, and a countermeasure has been required on the friction material side.
[0008] For example, Patent Document 4 discloses a friction material containing a binder, a friction modifier, and a fibrous base material, which does not contain a copper component and contains 10 to 20 volume % of at least one type of titanate compound having a plurality of convex shapes and 1 to 20 volume % of biosoluble inorganic fibers, thereby improving rust removal properties of a mating material.
[0009] However, as the use of regenerative brakes increases with the spread of electric and hybrid vehicles, the braking load on the friction material of conventional hydraulic brakes is reduced, resulting in a problem that sufficient rust removal properties cannot be obtained even when using technology such as that described in Patent Document 4.
[0010] Therefore, disk rotors made of stainless steel, which has excellent rust resistance, have come to be used.
[0011] Patent Document 5 discloses a four-wheel disk rotor manufactured from a stainless steel plate having a martensite structure or a mixed structure of a martensite phase and a ferrite phase.
[0012] Patent Document 6 describes a disk rotor for automobiles having a structure including martensite and carbonitrides, and optionally including ferrite.
[0013] Patent Document 7 describes the following composition by mass: C: 0.005-0.100%, Si: 0.01-1.00%, Mn: 0.010-3.00%, P: 0.040% or less, S: 0.0100% or less, Cr: 10.0-14.0%, N: 0.005-0.100%, V: 0.03-0.30%, Al: 0.001-0.050%, B: 0.0002-0.0050%, Ni: 0-2.00%, Cu: 0-2.00%, Mo: 0-1.00%, W: 0-1.00%, Ti: 0-0.40%, N b: 0-0.40%, Zr: 0-0.40%, Co: 0-0.400%, Sn: 0-0.40%, REM: 0-0.050% or less, Mg: 0-0.0100%, Ca: 0-0.0100%, Sb: 0-0.50%, Ta: 0-0.3000%, Hf: 0-0.3000%, Ga: 0-0.1000%, the balance being Fe and impurities, the metal structure being a ferrite phase, and carbonitrides having a circle-equivalent diameter of 0.3 μm or more are present in an arbitrary cross section at 10-50 pieces / 100 μm 2 The present invention describes a disk rotor for an automobile, which is made of a stainless steel plate and is characterized by the presence of
[0014] In light of this background, there is a demand for a friction material made of a friction material composition that does not contain a copper component and is compatible with disc rotors made of stainless steel, which has excellent rust resistance. However, it has been revealed that when the friction material becomes hot, the organic matter contained in the friction material, such as the binder and organic friction modifier, becomes susceptible to thermal decomposition, and the decomposed organic matter becomes interposed on the friction surface, reducing the stability of the braking effect. In addition, it has been revealed that the thermal decomposition of the binder significantly reduces the strength of the friction material, thereby reducing the wear resistance of the friction material. [Prior art documents] [Patent documents]
[0015] [Patent Document 1] JP 2017-57312 A [Patent Document 2] JP 2018-162385 A [Patent Document 3] Japanese Patent Application Publication No. 2-134425 [Patent Document 4] JP 2017-149971 A [Patent Document 5] JP 2016-117925 A [Patent Document 6] JP 2019-173086 A [Patent Document 7] JP 2019-178419 A Summary of the Invention [Problem to be solved by the invention]
[0016] The present invention aims to provide a friction pair consisting of a disc brake pad equipped with a friction material made of a friction material composition that contains a binder, a fiber base material, and a friction modifier, but does not contain a copper component or iron-based metal fibers, and a stainless steel disc rotor, which friction pair has excellent braking effectiveness stability and wear resistance of the friction material. [Means for solving the problem]
[0017] As a result of extensive investigations, the inventors have discovered that in a friction pair consisting of a disc brake pad equipped with a friction material made of a friction material composition that contains a binder, a fibrous base material, and a friction modifier, but does not contain a copper component or iron-based metal fibers, and a stainless steel disc rotor, it is possible to obtain a friction pair having excellent braking effectiveness stability and wear resistance of the friction material by using a friction material composition that does not contain any metal fibers other than iron-based metal fibers, and that contains a specific amount of a carbonaceous lubricant and a specific amount of an inorganic friction modifier having a Mohs hardness of 6 or more as the friction modifier, and by setting the thermal conductivity of the friction material within a specific range, thereby completing the present invention.
[0018] The present invention relates to a friction pair consisting of a disc brake pad having a friction material made of a friction material composition containing a binder, a fiber base material, and a friction modifier, but not containing a copper component or iron-based metal fibers, and a stainless steel disc rotor, and is based on the following technology.
[0019] (1) A friction pair comprising a disc brake pad having a friction material made of a friction material composition containing a binder, a fibrous base material, and a friction modifier, but containing no copper component or iron-based metallic fibers, and a stainless steel disc rotor, wherein the friction material composition does not contain any metallic fibers other than iron-based metallic fibers, the friction modifiers include 10 to 15 wt % of a carbonaceous lubricant based on the total amount of the friction material composition, and 15 to 30 wt % of an inorganic friction modifier having a Mohs hardness of 6 or more based on the total amount of the friction material composition, and the thermal conductivity of the friction material is 1.2 to 3.0 W / m K.
[0020] (2) The friction pair according to (1), wherein the carbonaceous lubricant is at least one selected from the group consisting of artificial graphite, natural graphite, crushed graphite sheet powder, petroleum coke, coal coke, elastic graphitized carbon, and crushed polyacrylonitrile oxide fiber powder.
[0021] (3) The carbonaceous lubricant is a friction pair according to (2) comprising crushed graphite sheet powder, petroleum coke, and elastic graphitized carbon.
[0022] (4) The friction couple according to any one of (1) to (3), wherein the friction material composition contains 13 to 28% by weight of zirconium oxide having an average particle size of 0.5 to 8 μm as part of the inorganic friction modifier having a Mohs hardness of 6 or more. Effect of the Invention
[0023] According to the present invention, it is possible to provide a friction pair consisting of a disc brake pad equipped with a friction material made of a friction material composition that contains a binder, a fiber base material, and a friction modifier, but does not contain a copper component or iron-based metal fibers, and a stainless steel disc rotor, which has excellent braking performance and wear resistance of the friction material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] A stainless steel disc rotor has a smaller thermal conductivity and thermal diffusivity than a cast iron disc rotor, and stainless steel has a slightly larger specific gravity than cast iron, but is slightly stronger. For this reason, if a stainless steel disc rotor is to have the same weight and strength as a cast iron disc rotor, it is designed to be thinner. This reduces the heat capacity of the disc rotor, making it easier for the disc rotor to store heat, and the temperature of the friction material also tends to be high.
[0025] When the friction material becomes hot, the organic matter contained in the friction material, such as the binder and organic friction modifier, becomes easily thermally decomposed, and the decomposed organic matter becomes interposed on the friction surface, which reduces the braking effect stability. In addition, the thermal decomposition of the binder significantly reduces the strength of the friction material, which reduces the wear resistance of the friction material.
[0026] In the present invention, a friction pair is provided, which is composed of a disc brake pad having a friction material made of a friction material composition that contains a binder, a fibrous base material, and a friction modifier, but does not contain a copper component or iron-based metal fibers, and a stainless steel disc rotor, and which uses a friction material composition that does not contain any metal fibers other than iron-based metal fibers, and which contains, as a friction modifier, 10 to 15 wt % of a carbonaceous lubricant based on the total amount of the friction material composition, and 15 to 30 wt % of an inorganic friction modifier having a Mohs hardness of 6 or more based on the total amount of the friction material composition, and which has a thermal conductivity of 1.2 to 3.0 W / m K.
[0027] By adding a relatively large amount of a carbonaceous lubricant as a friction modifier to the total amount of the friction material composition and by controlling the thermal conductivity of the friction material to a specific range, it is possible to impart heat dissipation properties to the friction material.
[0028] In this specification, the thermal conductivity of the friction material is measured by cutting out a friction material portion from a final disc brake pad product and measuring the thermal conductivity by a hot wire method using rapid thermal conductivity measurement.
[0029] By setting the content of the carbonaceous lubricant and the thermal conductivity of the friction material within the above ranges, the heat dissipation property of the friction material is improved and the temperature rise of the friction material can be suppressed, which results in suppression of thermal decomposition of the organic matter contained in the friction material, and also improves the wear resistance due to the lubricating effect of the carbonaceous lubricant.
[0030] However, simply adding a relatively large amount of carbonaceous lubricant reduces the braking stability due to the lubricating action of the carbonaceous lubricant. Therefore, in order to offset the lubricating action caused by adding the carbonaceous lubricant, an inorganic friction modifier having a Mohs hardness of 6 or more is added as a friction modifier in an amount of 15 to 30% by weight based on the total amount of the friction material composition.
[0031] By setting the content of the inorganic friction modifier having a Mohs hardness of 6 or more contained in the friction material composition within the above range, a grinding action on the disc rotor can be obtained, and excellent braking effectiveness and stability can be obtained even when a relatively large amount of carbonaceous lubricant is added.
[0032] In the present invention, the Mohs hardness scale used is the old Mohs hardness scale, which is expressed as "1. talc, 2. gypsum, 3. calcite, 4. fluorite, 5. apatite, 6. orthoclase, 7. quartz, 8. topaz, 9. corundum, 10. diamond."
[0033] The carbonaceous lubricant may be one or more selected from the group consisting of artificial graphite, natural graphite, crushed graphite sheet powder, petroleum coke, coal coke, elastic graphitized carbon, and crushed polyacrylonitrile oxide fiber powder. In particular, it is preferable to use a combination of three types of materials: crushed graphite sheet powder, petroleum coke, and elastic graphitized carbon.
[0034] Graphite sheet pulverized powder is a raw material obtained by thermally expanding natural graphite after acid treatment, forming the expanded graphite into a sheet using a roll press, and pulverizing the graphite sheet. Elastic graphitized carbon is a raw material obtained by graphitizing a carbonaceous raw material at 1900°C to 2700°C, stopping the graphitization degree at 80 to 95%.
[0035] The inorganic friction modifier having a Mohs hardness of 6 or more can be selected from the group consisting of iron oxide, magnesium oxide, zirconium oxide, silicon dioxide, zirconium silicate, gamma-alumina, alpha-alumina, silicon carbide, glass fiber, biosoluble ceramic fiber, rock wool, basalt fiber, etc., and can be used alone or in combination of two or more thereof.
[0036] It is preferable to add zirconium oxide having an average particle size of 0.5 to 8 μm as part of an inorganic friction modifier having a Mohs hardness of 6 or more, which is added in an amount of 15 to 30% by weight based on the total amount of the friction material composition, and the content of zirconium oxide is preferably 13 to 28% by weight based on the total amount of the friction material composition.
[0037] In this specification, the average particle size is the value of the 50% particle size measured by a laser diffraction particle size distribution measurement method.
[0038] <Friction material composition> The friction material used in the friction couple of the present invention is made of a friction material composition that contains the above-mentioned carbonaceous lubricant, the above-mentioned inorganic friction modifier having a Mohs hardness of 6 or more, as well as a binder, a fibrous base material, and a friction modifier that are typically used in friction materials.
[0039] Examples of the binder include binders that are commonly used in friction materials, such as straight phenolic resin, acrylic rubber modified phenolic resin, silicone rubber modified phenolic resin, nitrile rubber modified phenolic resin, cashew oil modified phenolic resin, aralkyl modified phenolic resin (phenol aralkyl resin) obtained by reacting phenols, aralkyl ethers, and aldehydes, acrylic rubber dispersed phenolic resin, silicone rubber dispersed phenolic resin, and fluoropolymer dispersed phenolic resin, and these may be used alone or in combination of two or more.
[0040] The content of the binder is preferably 4 to 9% by weight, and more preferably 6 to 8% by weight, based on the total amount of the friction material composition.
[0041] Examples of the fiber base material include organic fibers that are commonly used in friction materials, such as aramid fibers, acrylic fibers, cellulose fibers, and poly-paraphenylene benzobisoxazole fibers. These may be used alone or in combination of two or more.
[0042] The content of the fibrous base material is preferably 1 to 5% by weight, and more preferably 2 to 4% by weight, based on the total amount of the friction material composition.
[0043] As the friction modifier, a lubricant, an inorganic friction modifier, or an organic friction modifier can be used.
[0044] In addition to the above carbonaceous lubricants, examples of the lubricant include metal sulfide lubricants such as tin sulfide, molybdenum disulfide, iron sulfide, bismuth sulfide, zinc sulfide, and composite metal sulfides. These may be used alone or in combination of two or more.
[0045] The content of the lubricant, including the carbonaceous lubricant, is preferably 10 to 18% by weight, and more preferably 11 to 16% by weight, based on the total amount of the friction material composition.
[0046] In addition to the above-mentioned inorganic friction modifiers having a Mohs hardness of 6 or more, examples of the inorganic friction modifier include calcium hydroxide, calcium carbonate, barium sulfate, talc, dolomite, zeolite, calcium silicate hydrate, columnar titanate, plate-like titanate, particulate titanate, scaly titanate, irregular titanate having a plurality of protrusions (titanate includes potassium titanate, lithium potassium titanate, magnesium potassium titanate, sodium titanate, etc.), wollastonite, sepiolite, and the like, and these may be used alone or in combination of two or more.
[0047] The content of the inorganic friction modifier, including inorganic friction modifiers having a Mohs hardness of 6 or more, is preferably 60 to 82% by weight, and more preferably 65 to 76% by weight, based on the total amount of the friction material composition.
[0048] Examples of the organic friction modifier include cashew dust, ground tire tread rubber powder, polytetrafluoroethylene powder, and organic friction modifiers that are commonly used in friction materials, such as vulcanized or unvulcanized rubber powders, such as acrylic rubber, isoprene rubber, nitrile butadiene rubber, styrene butadiene rubber, butyl rubber, and silicone rubber. These may be used alone or in combination of two or more.
[0049] The content of the organic friction modifier is preferably 3 to 8% by weight, and more preferably 5 to 7% by weight, based on the total amount of the friction material composition.
[0050] <Method of manufacturing disc brake pads> The disc brake pad according to the present invention typically comprises: A mixing step of uniformly mixing the friction material composition (friction material raw material) in a predetermined amount using a mixer to obtain a friction material raw material mixture; A heat and pressure molding process in which the obtained friction material raw material mixture is layered on a back plate that has been separately washed, surface-treated, and coated with an adhesive, and then the layered mixture is placed in a thermoforming mold and heated and pressurized to form the mixture. a heat treatment step in which the obtained molded product is heated to complete the curing reaction of the binder; Painting process, where paint is applied by spray painting or electrostatic powder coating; The paint baking process involves baking the paint. A polishing process to form a friction surface using a rotating grindstone; It is manufactured through the process. In some cases, the manufacturing process may be carried out in the following order after the heat and pressure molding process: painting, a heat treatment process which also serves as painting baking, and a polishing process.
[0051] If necessary, before the heat and pressure molding process, a granulation step of granulating the friction material raw material mixture; A kneading step of kneading the friction material raw material mixture; a preforming step in which the friction material raw material mixture or the granulated product obtained in the granulating step and the kneaded product obtained in the kneading step are charged into a preforming mold to form a preforming product; may be carried out, and a scorching step may be carried out after the hot-press molding step.
[0052] <Stainless steel disc rotor> As the stainless steel disc rotor, for example, a martensitic stainless steel disc rotor or a ferritic stainless steel disc rotor can be used. EXAMPLES
[0053] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples.
[0054] [Method of manufacturing friction materials of Examples 1 to 14 and Comparative Examples 1 to 5] The friction material compositions shown in Tables 1 and 2 were charged into a Lödige mixer and mixed for 5 minutes to obtain a friction material composition mixture. This friction material composition mixture was pressed in a molding die at 30 MPa for 10 seconds to obtain a friction material preform. This friction material preform was placed on a steel back plate that had been previously cleaned, surface-treated, and coated with an adhesive, and molded in a thermoforming die at a molding temperature of 150°C and a molding pressure of 40 MPa for 10 minutes to obtain a friction material molded product. This friction material molded product was heat-treated (post-cured) for 5 hours at 200°C, and then polished to form a friction surface, to produce a disc brake pad for a passenger vehicle.
[0055] [Table 1]
[0056] [Table 2]
[0057] Furthermore, the friction material of the disc brake pad was cut into a size of 25 mm×15 mm×15 mm to obtain test pieces of Examples 1-14 and Comparative Examples 1-5.
[0058] Table 3 shows the test conditions, mating material, evaluation items, and evaluation criteria used to verify the braking stability and wear resistance of the friction material using these test pieces.
[0059] [Table 3]
[0060] Table 4 shows the "evaluation items" and "evaluation criteria" for the "product appearance" of these test pieces. Note that the "product" here refers to the final product, the "disc brake pad."
[0061] [Table 4]
[0062] Tables 5 and 6 show the evaluation results of "stability of braking effectiveness," "wear resistance of friction material," and "product appearance" shown in Tables 3 and 4 for each of the examples and comparative examples.
[0063] [Table 5]
[0064] [Table 6]
[0065] It can be seen from Tables 5 and 6 that the friction materials satisfying the conditions of the present invention have good braking stability, wear resistance and product appearance. [Industrial Applicability]
[0066] According to the present invention, in a friction pair consisting of a disc brake pad equipped with a friction material made of a friction material composition containing a binder, a fiber base material, and a friction modifier, but not containing a copper component or iron-based metal fibers, and a stainless steel disc rotor, it is possible to provide a friction pair having excellent braking effectiveness stability, friction material wear resistance, and product appearance, and the friction pair is of extremely high practical value.
Claims
1. A friction pair comprising a disc brake pad having a friction material made of a friction material composition containing a binder, a fibrous base material, and a friction modifier, but containing no copper component and no iron-based metal fibers, and a stainless steel disc rotor, wherein the friction material composition does not contain any metal fibers other than iron-based metal fibers, the friction modifiers include 10 to 15 wt % of a carbonaceous lubricant based on the total amount of the friction material composition, and 15 to 30 wt % of an inorganic friction modifier having a Mohs hardness of 6 or more based on the total amount of the friction material composition, zirconium oxide is contained as part of the inorganic friction modifier, and the thermal conductivity of the friction material is 1.2 to 3.0 W / m K.
2. 2. The friction pair according to claim 1, wherein the carbonaceous lubricant is at least one selected from the group consisting of artificial graphite, natural graphite, crushed graphite sheet powder, petroleum coke, coal coke, elastic graphitized carbon, and crushed polyacrylonitrile oxide fiber powder.
3. 3. The friction pair according to claim 2, wherein said carbonaceous lubricant comprises crushed graphite sheet powder, petroleum coke and elastic graphitized carbon.
4. A friction couple as described in any one of claims 1 to 3, characterized in that the average particle diameter of the zirconium oxide is 0.5 to 8.0 μm.
Citation Information
Patent Citations
Disk rotor material
JP1990134425A
Friction material
JP2004035871A
Frictional material composition and frictional material
JP2015093934A
Friction material composition, friction material, and friction member
JP2016079251A
Friction material composition, friction material, and friction member
JP2016079252A